EFFECT OF ACUTE IRRADIATION ON MORPHOLOGICAL FEATURES OF THE LUNGS - Rakhmatovna , Akhmatova Gulrukh (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Background: Acute radiation exposure impacts human health variably depending on the frequency, duration, and radiation sensitivity of different organs. Specific Background: While immune organs, mucous membranes, exo- and endocrine glands, and gonads are known to be highly sensitive to acute radiation, less is understood about the specific effects on less sensitive organs such as the lungs. Knowledge Gap: Despite established knowledge on the sensitivity of various organs to radiation, there is limited research focusing on the morphological changes occurring in the lungs as a result of acute radiation exposure. Aims: This study aims to investigate the morphological alterations in lung tissue following acute radiation exposure to better understand its impact on this organ. Results: The study reveals distinct morphological changes in the lungs under acute radiation conditions, including alterations in cellular structure and tissue integrity. These findings highlight the specific effects of radiation on lung tissue compared to other less sensitive organs. Novelty: This research provides new insights into the impact of acute radiation on lung morphology, contributing to a more comprehensive understanding of radiation effects beyond the commonly studied highly sensitive organs. Implications: Understanding the morphological changes in the lungs due to acute radiation exposure is crucial for improving radiation protection strategies and treatment protocols for individuals exposed to high levels of ionizing radiation.